STUDI ANALISIS KODIFIKASI HADIS - Agus Salim (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
Hadith is the second source of Islamic law. At the first, prophet Muhammad saw. forbade writing hadith. Because at this time the Qur’an had not been astablished yet, the prophet forbed the writing hadith. Because fear mixes between hadith and Quran. However, there were friends who wrote and memorized it. In the caliph ‘Umar bin ‘Abdul Aziz, he ordered to collect hadith officially. So, at this period hadiths were officially recorded.